Inclusive education and the implementation of the Decree-Law n.º 54/2018 - Duarte, Joaquina (Aprender, 2023)
Decree No. 54/2018 (DL), with the first amendment by Law No. 116/2019, establishes the principles and standards that guarantee inclusion, as a process that aims to respond to the diversity of the public school. Like all educational changes, this regulation presents a set of modifications at a structural, organizational and pedagogical level, that caused some concern in the faculty. The introduction of this legal regulations, despite being under public discussion, did not allowed schools space to take ownership of it before its implementation. Thus, discussions, doubts and concerns about the introduced changes have arisen. In this context has emerged the reason for this study, which aims to understand what constraints still exist in schools. The data collection instruments for analyzing interactions between teachers in the period between 2018 and 2020, explained in “Espaço 54 - Inclusive Education Support Group”, created on the social network Facebook. Having analyzed the results obtained, we can conclude that the lack of training and resources, as well as the organizational culture, are weaknesses that we can find in the implementation of inclusive education. There is still a lot to be explored in order to build collective responsibility in the (re)construction of a school for everyone, to everyone and with everyone.
Keywords: DL 54/2018; inclusive education; diversity